Innovation ecosystems in small countries – The case of Luxembourg - Nico Binsfeld; Jason Whalley (International Telecommunications Society (ITS), 2019)
Since it emerged at the start of the decade, the ecosystem model of Martin Fransman (Fransman, 2010) has been widely applied to understand innovative processes within the information and communication technology (ICT) sector - see, for example, Binsfeld, Whalley, & Pugalis (2017b). The framework has recently been updated (Fransman, 2018) so that an innovation ecosystem is defined as "of a group of interdependent players and processes who together through their interactions, make innovation happen". He has also proposed a deeper examination of the dynamics of how innovation happens within innovation systems, and who is in charge of making innovation happen. This paper seeks to apply this evolved understanding of innovative processes to Luxembourg. More specifically, the paper will describe and comment about the evolution of the ICT ecosystem in recent years. The paper will also present and reflect on a series of recent government initiatives that have been launched with the intention of stimulating the development of the ecosystem. Through such an approach, we will demonstrate the pivotal role played by the government as the main driver behind innovation in the ecosystem. The paper also outlines Luxembourg's national skills strategy and explores the degree to which these various initiatives may be integrated together.
Keywords: 330